2021
DOI: 10.1590/0004-282x-anp-2020-0409
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Parkinson’s disease in Brazil: a systematic review of monogenic forms

Abstract: Background: Increasing numbers of mutations causing monogenic forms of Parkinson's disease (PD) have been described, mostly among patients in Europe and North America. Since genetic architecture varies between different populations, studying the specific genetic profile of Brazilian patients is essential for improving genetic counseling and for selecting patients for clinical trials. Objective: We conducted a systematic review to identify genetic studies on Brazilian patients and to set a background for futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(9 reference statements)
0
5
0
2
Order By: Relevance
“…It should be emphasized that very few studies have been published on a large-scale analysis of multiple genes. Thus, a metaanalysis covering all major PD genes in Brazilian patients was conducted in [42] revealing that the most frequent point mutations were in the LRRK2 gene (2.5% of patients, with the p.Gly2019Ser mutation being found in 2.2% of cases). Mutations in the parkin gene were found in 8.3% of patients [42].…”
Section: Monogenic Forms Of Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that very few studies have been published on a large-scale analysis of multiple genes. Thus, a metaanalysis covering all major PD genes in Brazilian patients was conducted in [42] revealing that the most frequent point mutations were in the LRRK2 gene (2.5% of patients, with the p.Gly2019Ser mutation being found in 2.2% of cases). Mutations in the parkin gene were found in 8.3% of patients [42].…”
Section: Monogenic Forms Of Parkinson's Diseasementioning
confidence: 99%
“…Thus, a metaanalysis covering all major PD genes in Brazilian patients was conducted in [42] revealing that the most frequent point mutations were in the LRRK2 gene (2.5% of patients, with the p.Gly2019Ser mutation being found in 2.2% of cases). Mutations in the parkin gene were found in 8.3% of patients [42]. In Ireland, the analysis was limited to mutations in the PRKN, DJ1, and PINK1 genes and patients with the early onset PD, and only mutations in the PRKN gene were detected in 6.9% of the examined patients [31].…”
Section: Monogenic Forms Of Parkinson's Diseasementioning
confidence: 99%
“…However, the absence of mandatory PD notification complicates estimating its prevalence in the country. PD primarily affects the motor system, leading to various motor and non-motor symptoms that can deteriorate patients' quality of life [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…11,[13][14][15][16] The frequency of monogenic parkinsonism in populations such as those in Latin America is understudied, with only 10% of all research on the genetics of parkinsonism being conducted in this region. 17,18 Latinos are a heterogeneous population that typically exhibits a three-way admixture pattern, resulting from contributions from African, European, and Native American ancestry. Previous studies have shown differences in the frequency of specific monogenic parkinsonism between the Latino population and others.…”
mentioning
confidence: 99%
“…However, most of the published data on monogenic PD and related parkinsonian syndromes derived from patients of European and Asian ancestry 11,13–16 . The frequency of monogenic parkinsonism in populations such as those in Latin America is understudied, with only 10% of all research on the genetics of parkinsonism being conducted in this region 17,18 . Latinos are a heterogeneous population that typically exhibits a three‐way admixture pattern, resulting from contributions from African, European, and Native American ancestry.…”
mentioning
confidence: 99%